Bioinformatics and functional analysis of an Entamoeba histolytica mannosyltransferase necessary for parasite complement resistance and hepatical infection. - Christian Weber; Samantha Blazquez; Sabrina Marion; Christophe Ausseur; Divya Vats; Mickael Krzeminski; Marie-Christine Rigothier; Rachid C Maroun; Alok Bhattacharya; Nancy Guillén (Public Library of Science (PLoS), 2008)
The glycosylphosphatidylinositol (GPI) moiety is one of the ways by which many cell surface proteins, such as Gal/GalNAc lectin and proteophosphoglycans (PPGs) attach to the surface of Entamoeba histolytica, the agent of human amoebiasis. It is believed that these GPI-anchored molecules are involved in parasite adhesion to cells, mucus and the extracellular matrix. We identified an E. histolytica homolog of PIG-M, which is a mannosyltransferase required for synthesis of GPI. The sequence and structural analysis led to the conclusion that EhPIG-M1 is composed of one signal peptide and 11 transmembrane domains with two large intra luminal loops, one of which contains the DXD motif, involved in the enzymatic catalysis and conserved in most glycosyltransferases. Expressing a fragment of the EhPIG-M1 encoding gene in antisense orientation generated parasite lines diminished in EhPIG-M1 levels; these lines displayed reduced GPI production, were highly sensitive to complement and were dramatically inhibited for amoebic abscess formation. The data suggest a role for GPI surface anchored molecules in the survival of E. histolytica during pathogenesis.